Hubungan Keperdataan Antara Anak Luar Kawin Dan Orangtuanya: Studi Perbandingan Dengan Hukum Keluarga Di Belanda - Latumahina, Rosalinda Elsina (Jurnal Hukum & Pembangunan, 2018)
Post Constitutional Court Decision No. 46 / PUU-VIII / 2010 dated February 17, 2012 on the amendment of Article 43 paragraph (1) of Marriage Act, many questions still raised regarding the implementation of the aforementioned article to establish civil relations between children born out of wedlock and their parents, especially with the father. The verdict by Supreme Court that rejected the lawsuit by Hj. Aisha Mochtar regarding legal status of her son, as well as several other court decisions indicate that there are various interpretations of the Article so that Article 43 paragraph (1) of Marriage Act cannot be implemented properly. It makes the author feel the necessity to do a comparative study with other country. The option to do a comparative study imposed on Dutch Law because the Dutch Civil Code / Nieuw Burgelijk Wetboek prevailing in the Netherlands today is the development of BW which is still in force in Indonesia. The results shows that the regulation of civil between children born out of wedlock and their parents in the Netherlands has given a better legal protection and legal certainty for children born out of wedlock than the applicable law in Indonesia.